An Experimental Investigation into Cross-National Mail Survey Response Rates - Jobber, David; Saunders, John (Journal of International Business Studies, 1988)
This study investigates the effects of foreign and domestic source manipulations on cross-national response rates of business people in two countries: the United States and Britain. The hypothesis that managers from the U.S.A. are more likely to respond than those from Britain is also tested. Results suggest that foreign source effects do not raise response rates. For British managers, findings suggest that higher compliance results from the ‘domestic’ source. Responses from USA managers were no higher than from their British counterparts. The implications of these findings for cross-national mail surveys are discussed.